Neuroplasticity. How regular physical activity influences the brain's structure and function - Julia Dołęga; Łukasz, Stanisław Papież; Piotr Mól; Tomasz Maciejczyk; Antoni Sieńko; Małgorzata Łabuś; Bartłomiej Zabawa; Patrycja Hudzińska; Karol Krzykawski; Jakub Sadowski (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Physical activity is associated with a reduced risk of chronic diseases, including cardiovascular disease, obesity, type 2 diabetes, and cognitive decline. Exercise supports brain health and cognitive function, with potential benefits for neuroplasticity-the brain's ability to reorganize in response to demands and injury. Materials and methods: A literature review was conducted using Pubmed and Google Scholar database with following search terms: "physical activity", "neurogenesis", "BDNF", "neuroplasticity" and "cognitive function". State of knowledge: Neuroplasticity, the brain's ability to reorganize and form new connections in response to learning or injury, is supported at the molecular level by various factors (e.g. BDNF or VEGF). Aerobic and resistance exercises have been linked to increased gray and white matter volumes, especially in regions critical to memory and executive function. These effects are valuable in preventing cognitive decline and improving mental health. Current research has also shown that the impact of exercise on neuroplasticity can be augmented through consistent, high-intensity activity, which supports neuroplasticity through hormone modulation. Furthermore, emerging technologies like neuroimaging have advanced our understanding of the mechanisms underlying exercise-induced brain adaptation, which holds promise for personalized interventions.  Conclusions: This review focuses on the preventive and therapeutic potential of physical activity for neurological health, highlighting the need for continued research into how different forms of physical activity can influence neuroplasticity.